-
Notifications
You must be signed in to change notification settings - Fork 2
/
Copy pathchapter.tex
232 lines (225 loc) · 14.5 KB
/
chapter.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
\documentclass{report}
\usepackage[utf8]{inputenc}
\usepackage{amssymb}
\usepackage{auto-pst-pdf}
\usepackage{amsmath}
\usepackage{pstricks}
\usepackage{pst-plot}
\usepackage{framed}
\usepackage{gensymb}
\title{Maths in \LaTeX}
\author{Ashu \& Amitt}
\date{\today}
\begin{document}
\maketitle
\tableofcontents
\chapter{Homogeneous function and Euler's theorem}
\textbf{\textit{Question}}: Explain homogeneous functions and derive euler's theorem on homogeneous function.
\\[12pt]
\noindent \textbf{\textit{Solution}}:
A function \(f(x,y)\) is said to be homogeneous of degree (or order) $n$ in the variable $x$ and $y$ if it can be expressed in the form \(x^n\phi(\frac{y}{x})\) or \(y^n\phi(\frac{x}{y})\). \\[8pt]
An alternative test for a function f(x,y) to be homogeneous of degree(or order) $n$ is that \\
\hspace*{5em} \(f(tx,ty)=t^nf(x,y)\) \\
\\[8pt]
For example,if \(f(x,y)=\dfrac{x+y}{\sqrt{x}+\sqrt{y}}\),then
\\[8pt]
\hspace*{5em} \(f(x,y)=\dfrac{x\left(1+\dfrac{y}{x}\right)}{\sqrt{x}(1+\sqrt{\frac{y}{x}}}=x^\frac{1}{2}\phi\left(\dfrac{y}{x}\right)\)
\\[8pt]
$\Rightarrow$ $f(x,y)$ is a homogeneous function of degree $\frac{1}{2}$ in $x$ and $y$. \\[8pt]
\hspace*{5em} $f(x,y)=\dfrac{y(1+\dfrac{x}{y})}{\sqrt{y}\left(1+\sqrt{\dfrac{x}{y}}\right)}=y^\frac{1}{2}\phi(\dfrac{x}{y})$
\\[8pt]
$\Rightarrow$ $f(x,y)$ is a homogeneous function of degree $\frac{1}{2}$ in $x$ and $y$. \\[8pt]
\textbf{\underline{Euler's theorem on homogeneous function}}\\[8pt]
{\itshape If u is homogeneous function of degree n in xand y, then \(\dfrac{\partial{u}}{\partial{x}} + y\dfrac{\partial{u}}{\partial{y}}=nu\).}
\\[8pt]
Since u is a homogeneous function of degree n in x and y, it can be expressed
\begin{align}
u =& x^nf\left(\dfrac{y}{x}\right) \\
\dfrac{\partial{u}}{\partial{x}}=&nx^n-1f\left(\dfrac{y}{x}\right)+x^n f'\left(\dfrac{y}{x}\right).\left(-\dfrac{y}{x^2}\right) \\
\Rightarrow x\dfrac{\partial{u}}{\partial{x}}=&nx^nf\left(\dfrac{y}{x})-x^n-1 yf' \frac{y}{x}\right) \\
\dfrac{\partial{u}}{\partial{y}}=&x^nf'\left(\dfrac{y}{x}\right).\dfrac{1}{x}=x^n-1 f'\left(\dfrac{y}{x}\right) \\
\Rightarrow y\dfrac{\partial{u}}{\partial{y}}=&x^n-1yf'\left({\dfrac{y}{x}}\right)
\end{align}
Adding (1.1) and (1.3), we get \(x\dfrac{\partial{u}}{\partial{x}} + y\dfrac{\partial{u}}{\partial{y}}=nx^nf\left(\dfrac{y}{x}\right)=nu\).
\chapter{Maxima and Minima}
\textbf{\textit{Question}}: Examine the function \(x^3+y^3-3axy\) for maxima and minima.
\\[10pt]
\textbf{\textit{Solution}}:Here \(f(x,y)=x^3+y^3-3axy \\[8pt]
\hspace*{5em} f_x=3x^2-3ay,\: f_y=3y^2-3ax,\: f_{xx}=6x,\: f_xy=-3a,\: f_{yy}=6y \) \\[8pt]
Now for extreme values \qquad \(f_x=f_y=0\) \\[8pt]
$\Rightarrow$ \qquad $x^2-ay=0$ and $y^2-ax=0$ \\[8pt]
$\Rightarrow$ \qquad $y=\dfrac{x^2}{a}$ \\[8pt]
$\therefore$ $\dfrac{x^4}{a^2}-ax=0$\: or\: $x(x^2-a^2)=0$\: or\: $x=0$,\: a when \\[5pt]
$x=0$, $y=0$; when $x=a,y=a$ \\[8pt]
$\therefore$\: There are two stationary points $(0,0)$ and $(a,a)$ \\[8pt]
Now $rt-s^2=36xy-9a^2$ \\[8pt]
\textbf{At (0,0)}\: \(rt-s^2=-9a^2 < 0\) \\[8pt]
$\Rightarrow$ \qquad There is no extreme value at \((0,0)\). \\[8pt]
\textbf{At (a,a)}\: \(rt-s^2=36a^2-9a^2=27a^2 > 0\) \\[8pt]
$\Rightarrow$ \qquad $f(x,y)$ has extreme value at (a,a). \\[8pt]
Now \(r=6a^2\) \\[8pt]
If \(a>0\), \(r>0\) so that \(f(r,y)\) has minimum value at \((a,a)\). \\[8pt]
Minimum value=\(f(a,a)=a^3+a^3-3a^3=-a^3\) \\
\chapter{Curve Tracing}
\textbf{\textit{Question}}:Trace the curve \(x^3 + y^3 = 3axy\).
\\[10pt]
\textbf{\textit{Solution}}: The equation of the curve is \\
\hspace*{5em} \(x^3 + y^3 - 3axy=0\)\\[5pt]
1.\textbf{Symmetry}: The curve is neither symmetric about x-axis nor y-axis but about \(y=x\). \\[5pt]
2.\textbf{Origin}:The curve passess through the origin \(0,0\) and the tangents at the origin are given by \hspace*{3em} \(3axy=0\)
i.e. \(x=0,y=0\) i.e. x-axis and y-axis.\\[5pt]
3.\textbf{Domain and Range}: From above it is clear x and y both cannot be negative \(\because\) then L.H.S will be negative but R.H.S will be positive which is impossible \\
$\therefore$ no protion of the curve will lie in $3^{rd}$ quadrant. \\[5pt]
4.\textbf{Points of Intersection}: Curve meets x-axis at $(0,0)$. Curve meets y-axis at $(0,0)$ $\therefore$\: the curve passes only thorugh $(0,0)$. \\[5pt]
Curve intersects\: \(y=x\)\: where\: \(x^3+x^3=3ax^2\)\: or\: \(2x^3 = 3ax^2\) or\: \(x=\dfrac{3a}{2}\)\: \(\therefore \) Points of intersection with \(y=x\) is \(\left(\dfrac{3a}{2},\dfrac{3a}{2}\right)\). \\[5pt]
\begin{pspicture}
% \psgrid{<->}(0,0)(-5,-5)(10,10)
\psaxes[linewidth=1.2pt,labels=all,ticks=all,linecolor=gray,tickcolor=gray]{<->}(0,0)(-5,-5)(10,10)
\psline[linestyle=dotted](0,0)(8,8)(-5,-5)
\psline[linestyle=dotted](7,0)(-3,10)(9,-2)
\psarc[linecolor=red]{->}(7,0){1}{0}{135}
\pscurve(-5,2.9)(0,0)(3.64,3)(3.5,3.5)(0.59,2)(0,0)(2.9,-5)
\psline(-6,3.7)(3.7,-6)
\rput[t]{0}(7.2,0.5){135\degree}
\rput[t]{0}(4.5,3.6){$(\frac{3a}{2},\frac{3a}{2})$}
\rput[b]{-47}(-4,1){Asymptote}
\rput[b]{-47}(1,-4){$x+y+a=0$}
\rput[b]{0}(3,-1){Tangent}
\rput[t]{90}(-1,4){Tangent}
\end{pspicture}
\\[200pt]
5.\textbf{Tangents}: To find the slope of tangent at \(\left(\dfrac{3a}{2},\dfrac{3a}{2}\right)\) diffrentiate given equation w.r.t x. \\[5pt]
\begin{align*}
3x^2+3y^2\dfrac{\mathrm{dy}}{\mathrm{dx}}=&3ax\dfrac{\mathrm{dy}}{\mathrm{dx}}+3ay \\
(y^2-ax)\dfrac{\mathrm{dy}}{\mathrm{dx}}=&ay-x^2 \\
(\dfrac{\mathrm{dy}}{\mathrm{dx}})=&\dfrac{ay-x^2}{y^-ax} \\
\dfrac{\mathrm{dy}}{\mathrm{dx}}_{(\frac{3a}{2},\frac{3a}{2})}=&\dfrac{\dfrac{3a^2}{2}-\dfrac{9a^2}{4}}{\dfrac{9a^2}{4}-\dfrac{3a^2}{2}}=-1 \\
\end{align*}
\(\therefore\) At \(\left(\dfrac{3a}{2},\dfrac{3a}{2}\right)\) slope of tangent = -1 \\
\(\therefore\) Tangent makes an angle of 135 with x-axis at \(\left(\dfrac{3a}{2},\dfrac{3a}{2}\right)\) \\
6.\textbf{Asymptotes}: Asymptotes of \(x^2 + y^3 = 3axy\) are given by putting \(x=1,y=m\) \\
\begin{align*}
\phi_3(m)=& 1+m^3 ,\phi'_3(m)=3m^2, \phi''_3(m)=6m \\
\phi_2(m) =& -3am, \phi'_2(m)=-3a, \\
\phi_3(m)=& 0\: given\: 1+m^3 = 0
\end{align*}
or \((1+m)(1-m+m^2)=0 \) only real value of m is -1. \\
\(\therefore\)\: Asymptote with slope \(m=-1\) is \(y=-x+c\) where c is given by \\
\begin{align*}
c\phi'_3(m)+\phi_2(m)=&0\: at\: m=-1 \\
c(3)+(-3a)(-1)=&0 \\
c(3)+(-3a)(-1)=&0 \\
\end{align*}
or $c+a=0 \therefore c=-a$ \\
$\therefore$ Asymptote is y=-x-a or x+y+a=0 \\
\chapter{Projectile Motion}
\textbf{\textit{Question}}To derive the equations for projectile motion, we assume that the projectile is moving along in a vertical plane and that the only force acting on the projectile is the constant force of gravity, which always points straight downward.
\noindent \textbf{\textit{Solution}}
We assume that the projectile is lauched from the origin at time t = 0 into the first quadrant with an initial velocity $\vec{v_0}$ .If $\vec{v_0}$ makes an angle $\alpha$ with the horizontal and the initial speed of the projectile is $v_{0} = |\vec{v_{0}}|$ , then \\
\hspace*{10 em}$\vec{v_{0}} = (v_{0}\cos\alpha)\vec{i} + (v_{0}\sin\alpha)\vec{j}$ and $\vec{r_{0}} = \vec{0}$ \\
By Newton's Second Law of Motion $F = m\vec{a}$, so\\[5pt]
\hspace*{10 em}$m\vec{a} = (-mg)\vec{j}$\\[5pt]
\hspace*{10 em}$\vec{a} = -g\vec{j}$\\[5pt]
\hspace*{10 em}$\frac{d^2\vec{r}}{dt^2}$ $= -g\vec{j}$\\[5pt]
Integrating twice and using the fact that $\vec{v}(0) = (v_{0}\cos\alpha)\vec{i} + (v_{0}\sin\alpha)\vec{j}$ and $\vec{r}(0) = \vec{0}$,we get\\[5pt]
\hspace*{10 em}$\vec{r}(t) = -\frac{1}{2}gt^2\vec{j} + \overrightarrow{v_{0}}t + \overrightarrow{r_{0}}$ \\[5pt]
\hspace*{10 em}$\vec{r}(t) = -\frac{1}{2}gt^2\vec{j} + ((v_{0}\cos\alpha)\vec{i} + (v_{0}\sin\alpha)\vec{j}) + \vec{0}$ \\[5pt]
\hspace*{10 em}$\vec{r}(t) = (v_{0}\cos\alpha)t\vec{i} + (-\frac{1}{2}gt^2 + (v_{0}\sin\alpha)t)\vec{j}$\\[5pt]
\begin{framed}
Ideal Projectile Motion Equation \\[5pt]
\hspace*{10 em}$\vec{r}(t) = (v_{0}\cos\alpha)t\vec{i} + (-\frac{1}{2}gt^2 + (v_{0}\sin\alpha)t)\vec{j}$\\[5pt]
\end{framed}
\begin{pspicture}
% \psgrid{<->}(0,0)(0,0)(20,20)
\psaxes[linewidth=1.2pt,labels=all,ticks=all,linecolor=gray,tickcolor=gray]{->}(0,0)(10,10)
\parabola[linecolor=blue](0,0)(5,9)
\psline(0,0)(7,7.5)
\psline{->}(7,7.5)(7,3.5)
\psline{->}(7,7.5)(7,3.5)
\psline{->}(7,7.5)(8.2,6)
\rput[t](7.7,7.5){$\vec{\textbf{v}}$}
\rput[t](7,3){$\vec{\textbf{a}}$}
\rput[t](4.3,4){$\vec{\textbf{r}}$}
\psarc{->}(0,0){2}{0}{47}
\rput[t](1.2,0.7){$\alpha\degree$}
\end{pspicture}
\\[100pt]
The angle $\alpha$ is the projectile'slaunch angle.The horizontal and vertical component's of position give the parametric equations \\
\hspace*{10 em} $ x = (v_{0}\cos\alpha)t$ and $ y = -\frac{1}{2}gt^2\vec{j} + (v_{0}\sin\alpha)t $ \\
where x is the distance downrange and y is altitude of the projectile at time t.
Height,Flight Time and Range \\
The projectile reaches its height point when its vertical velocity is zero, that is, when\\
\hspace*{10 em} $\frac{dy}{dt} = v_{0}\sin\alpha - gt = 0$ and $t = \frac{v_{0}\sin\alpha}{g}$\\
For this value of time, the altitude of the projectile is\\
\hspace*{10 em}$ y_{max} = v_{0}\sin\alpha(\frac{v_{0}\sin\alpha}{g}) -\frac{1}{2}g(\frac{v_{0}\sin\alpha}{g})^2 = \frac{(v_{0}\sin\alpha)^2}{2g}$\\
To find when the projectile lands when fired over horizontal ground, we set the vertical component equal to zero and solve for t.\\
\hspace*{10 em}$ -\frac{1}{2}gt^2 + (v_{0}\sin\alpha)t = 0$\\
\hspace*{10 em}$ t(-\frac{1}{2}gt + (v_{0}\sin\alpha)) = 0$\\
\hspace*{10 em}$ t = 0$ or $-\frac{1}{2}gt + (v_{0}\sin\alpha) = 0 $\\
\hspace*{10 em}$ t = 0$ or $\frac{1}{2}gt = (v_{0}\sin\alpha)$\\
\hspace*{10 em}$ t = 0$ or $ t = \frac{2v_{0}\sin\alpha}{g}$\\
To find the projectile's range, we find the value of the horizontal component when $t = \frac{2v_{0}\sin\alpha}{g}$\\
\hspace*{6 em} $ x =(v_{0}\cos\alpha)t = (v_{0}\cos\alpha)(\frac{2v_{0}\sin\alpha}{g}) = \frac{v^2_{0}2\sin\alpha\cos\alpha}{g} = \frac{v^2_{0}2\sin2\alpha}{g} $\\
The range is largest when $\sin\alpha = 1 $ or when $ 2\alpha = 90\degree$, $\alpha =45\degree$\\
\begin{framed}
Height, Flight Time and Range for Ideal Motion. \\
For ideal projectile motion when an object is launched from the origin over a horizontal surface with initial speed $v_{0}$ and launch angle $\alpha$: \\
\hspace*{2 em}Maximum Height $y_{max} = v_{0}\sin\alpha(\frac{v_{0}\sin\alpha}{g}) -\frac{1}{2}g(\frac{v_{0}\sin\alpha}{g})^2 = \frac{(v_{0}\sin\alpha)^2}{2g}$\\
\hspace*{10 em} Flight Time $t = \frac{2v_{0}\sin\alpha}{g}$\\
\hspace*{10 em} Range $x = \frac{v^2_{0}2\sin2\alpha}{g}$\\
\end{framed}
\chapter{Runge-Kutta Method}
\section{Runge-Kutta Method For Simultaneous First Order Equation}
Consider the simultaneous equation $\frac{dy}{dx} = f_{1}(x,y,z)$ with the initial conditions $y(x_{0}) = y_{0}$ and $z(x_{0}) = z_{0}$ .Now starting from $(x_{0},y_{0},z_{0})$ the increments $k$ and $l$ in $y$ and $z$ are given by the following formulae. \\ \\ \\
\hspace*{4 em}$k_{1} = hf_{1}(x_{0},y_{0},z_{0}); \hspace*{7.5 em} l_{1} = hf_{2}(x_{0},y_{0},z_{0})$\\ \\ \\
\hspace*{4 em}$k_{2} = hf_{1}(x_{0} + \frac{h}{2},y_{0}+ \frac{k_{1}}{2},z_{0}+ \frac{l_{1}}{2}); \hspace*{1 em} l_{2} = hf_{2}(x_{0}+ \frac{h}{2},y_{0}+ \frac{k_{1}}{2},z_{0}+ \frac{l_{1}}{2})$\\ \\ \\
\hspace*{4 em}$k_{3} = hf_{1}(x_{0}+ \frac{h}{2},y_{0}+ \frac{k_{2}}{2},z_{0}+ \frac{l_{2}}{2}); \hspace*{1 em} l_{3} = hf_{2}(x_{0}+ \frac{h}{2},y_{0}+ \frac{k_{2}}{2},z_{0}+ \frac{l_{2}}{2})$\\ \\ \\
\hspace*{4 em}$k_{4} = hf_{1}(x_{0} + h,y_{0} + k _{3},z_{0} + l_{3}); \hspace*{1 em} l_{4} = hf_{2}(x_{0} + h,y_{0} + k_{3},z_{0} + l_{3})$\\ \\ \\
\hspace*{4 em}$k = \frac{1}{6}(k_{1} + 2k_{2} + 2k{_3} + k{_4}); \hspace*{4 em} l = \frac{1}{6}(k_{1} + 2k_{2} + 2k{_3} + k{_4})$\\ \\ \\
Hence $y_{1} = y_{0} + k, z_{1} = z_{0} + l$\\ \\
To compute $y_{2} z_{2}$ we simply replace $x_{0},y_{0},z_{0}$ by $x_{1},y_{1},z_{1}$ in the above formulae. \\ \\
If we consider the the second order Runge-Kutta method, then\\
\hspace*{4 em}$k_{1} = hf_{1}(x_{0},y_{0},z_{0}); \hspace*{7.5 em} l_{1} = hf_{2}(x_{0},y_{0},z_{0})$\\ \\ \\
\hspace*{4 em}$k_{2} = hf_{1}(x_{0} + h,y_{0} + k _{1},z_{0} + l_{1}); \hspace*{1 em} l_{2} = hf_{2}(x_{0} + h,y_{0} + k_{1},z_{0} + l_{1})$\\ \\ \\
\hspace*{4 em}$k = \frac{1}{2}(k_{1} + k_{2}); \hspace*{9 em} l = \frac{1}{2}(k_{1} + k_{2})$\\ \\ \\
$\therefore$\hspace*{4 em}$y_{1} = y_{0} + k$ and $z_{1} = z_{0} + l$\\ \\ \\
\section{Runge-Kutta Method For Second Order Equation}
Consider the second order differential equation \\ \\
\hspace*{10 em} $ \frac{d^2y}{dx^2} = \phi\left[x,y,\frac{dy}{dx}\right]; \hspace*{2 em}y(x_{0}) = y_{0}; \hspace*{2 em}y'(x_{0}) = y'_{0}$\\ \\ \\
Let $\frac{dy}{dx} = z$, then $ \frac{d^2y}{dx^2} = \frac{dz}{dx}$\\ \\ \\
Substituting in $(1)$ , we get $ \frac{dz}{dx} = \phi\left[x,y,z\right]; \hspace*{2 em}y(x_{0}) = y_{0}; \hspace*{2 em}z(x_{0}) = z_{0}$ \\ \\ \\
$\therefore$ The problem reduces to solving the simultaneous euation \\ \\ \\
\hspace*{10 em}$\frac{dy}{dx} = z = f_{1}(x, y, z)$ \\ \\ \\
and \hspace*{10 em}$\frac{dz}{dx} = f_{2}(x, y, z)$ subject to $y(x_{0}) = y_{0}; \hspace*{1 em}z(x_{0}) = z_{0}$
\chapter{Area Between the Curves}
\textbf{\textit{Question}}:Determine the area of the region bounded by $x=-y^2+10$ and $x=(y-2)^2$. \\[8pt]
\noindent\textbf{\textit{Solution}}: \\
Fist we need intersection point \\[5pt]
\begin{align*}
-y^2+10=&(y-2)^2 \\
-y^2+10=&y^2-4y+4 \\
0=&2y^3-4y-6 \\
0=&2(y+1)(y-3)
\end{align*}
The intersection points are $y=-1$ and $y=3$. Here is sketch of the region. \\
\begin{pspicture}
\psaxes[labels=all,ticks=all]{->}(0,0)(-2,-2)(10,10)
%\pscustom[fillstyle=solid,fillcolor=green!60,linestyle=none]
% {
\pscurve[linecolor=red](6,4.45)(1,3)(0,2)(9,-1)(12.2,-1.5)
\pscurve[linecolor=blue](-2,3.5)(1,3)(10,0)(9,-1)(6,-2)
% }
\rput[t](5,3){$x=-y^2+10$}
\rput[t]{20}(4,4.5){$x=(y-2)^2$}
\end{pspicture}
\\[125pt]
This is definitely a region where the second area formula will be easier. If we used the first formula there would be three different regions that we’d have to look at. \\[5pt]
The area in this case is,
\begin{align*}
A=&\int_c^d(right function)-(left function)\mathrm{dy} \\
=&\int_{-1}^3-y^2+10-(y-2)^2\mathrm{dy} \\
=&\int_{-1}^3-2y^2+4y+6\mathrm{dy} \\
=&\left(-\dfrac{2}{3}y^3 + 2y^2 + 6y\right)\big|_{-1}^3 \\
=&\dfrac{64}{3} \\
\end{align*}
\end{document}